Pengaruh Model Pembelajaran Inquiri Melalui Keterampilan Proses Terhadap Hasil Belajar IPA di Kelas IV SDN Model Terpadu Madani Palu - Yane Maroangi; I Komang Werdhiana; Vanny, M. A. Tiwow (Mitra Sains, 2015)
The major problem of this research was that any students had under school minimum standard of mastery learning on their daily exam of Science concepts. The school minimum standard of mastery learning was 75%. Therefore, experimental research was conducted with the aim of implementation of learning method through skills process to improve learning outcomes of Science on students class IV at SDN Model Terpadu Madani Palu. Learning was focused on the integrated thematic learning through scientific approach and authentic assessment recommended by Curriculum 2013. The instruments were learning plans including learning scenarios, teacher and student activities observation sheets, and pretest and posttest. Results of the data analysis showed that learning by inquiry method through skills process improved an average posttest score to 6.15, while the learning mastery reached up 24.24%. The authentic assessment as the characteristic of scientific assessment on integrated science had an average attitude 3.30 (start developing) with the percentage average 82.72%. Teacher activities implemented reached an average 4.95 with the percentage average implemented 99.16% or very good implementation, and activities of 24 students implemented reached an average 4.69 with the percentage average implemented 93.89% or very good implementation. It can be concluded that the application of inquiry learning model through skills process improved the learning outcomes of Science through integrated thematic and authentic assessment approaches.